2012
DOI: 10.3138/ptc.2010-50
|View full text |Cite
|
Sign up to set email alerts
|

Continuing Education for Advanced Manual and Manipulative Physiotherapists in Canada: A Survey of Perceived Needs

Abstract: Purpose: Our purpose was to determine advanced manual and manipulative physiotherapists' (AMPTs') current use and awareness of continuing education (CE) opportunities; to establish their perceived CE needs by identifying facilitators and barriers to participation; and to explore the association of demographics with CE needs. Methods: A questionnaire was e-mailed to 456 registered members of the Canadian Academy of Manipulative Physiotherapy. Data analyses using frequencies and percentages of total responses an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Another strength of the study is that, compared with previous studies, 2 the stratified care education content provided was brief, but similar outcomes were obtained. Previous studies 53,54 have indicated that one of the most significant barriers to attending postprofessional education courses is time. Therefore, it was our intent to provide the necessary education for this study in reasonable intervals that also accommodated clinicians' schedules (ie, 8 hours over multiple sessions) in order to improve retention rates and be consistent with our pragmatic approach.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Another strength of the study is that, compared with previous studies, 2 the stratified care education content provided was brief, but similar outcomes were obtained. Previous studies 53,54 have indicated that one of the most significant barriers to attending postprofessional education courses is time. Therefore, it was our intent to provide the necessary education for this study in reasonable intervals that also accommodated clinicians' schedules (ie, 8 hours over multiple sessions) in order to improve retention rates and be consistent with our pragmatic approach.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…These factors include practitioner interest, educational needs, and barriers to and facilitators of the uptake of the new practice. 9,[20][21][22][23] Although studies have examined educational programs for DI in other provinces (e.g., Alberta, New Brunswick) and internationally, 24 as well as the outcomes of integrating advanced practitioners into health care systems, 5,8,9,[24][25][26] no studies to date have examined physiotherapists' specific interest in ordering DI.…”
mentioning
confidence: 99%
“…Moreover, we recognize that a response rate of 37% in the initial round represents the low end of acceptable response rates for surveys in general; 19 however, our response rates are very similar to those found in a study comparing mail surveys and internet-based surveys 33 and in other studies using webbased methods to survey OMPTs. 34 …”
Section: 30mentioning
confidence: 99%